PRODUCTION AND COMPARATIVE QUALITY EVALUATION OF CHIN-CHIN SNACKS FROM MAIZE, SOYBEAN AND ORANGE FLESHED SWEET POTATO FLOUR BLENDS (FUDMA JOURNAL OF SCIENCES, 2020)
Most snacks are prepared from basically cereal flours which are nutritionally inadequate. There is the need to complement the nutrient content of these snacks by varying the food sources. Chin-chin snacks were produced from composite flours of Maize, soybean and OFSP with the following formation; sample A (50%: 25%: 25%), B (25%: 25%: 50%), C (25%: 50%: 25%), D (0%: 50%: 50%) and E (50%: 50%: 0%). Wheat flour (100%) served as the control F. The flour bends were analysed for functional properties while the chin-chin snacks were analysed for their nutrient and sensory qualities. The result of functional properties of the flours showed that bulk density of wheat flour (F) was the highest (0.746 g/ml). OFSP flour enhanced the water absorption capacity of the flour blends. Flour blends with soybean recorded higher values in foam capacity (11.20 - 22.55%). In proximate composition, the moisture was low (3.80 – 4.80%) in the chin-chin. Higher fibre content (2.60 - 4.20%) was obtained in samples containing higher proportion (50%) of OFSP. Samples D (19.38%) and C (18.80%) with higher soybean, recorded higher protein values. The mineral and the vitamin contents of snacks from composite flours were higher than that of the control F. Vitamin B1, B2, B3 and β-carotene contents of the snacks were enhanced by OFSP. The sensory evaluation showed preference for snack F (100% wheat flour) followed by snack A (50% maize, 25% soybean and 25% OFSP). However, improved nutrient dense chin-chin snacks were produced from the composite flours.
Keywords: Proximate; Antinutrients; Phytochemicals; Composite; Sensory